Upper GI Endoscopy in a Patient with Submucous Fibrosis - Kaushik Bhattacharya; Sayan Manna (National Board of Examinations Journal of Medical Sciences, 2025)
Upper gastrointestinal (GI) endoscopy in a patient with submucous fibrosis is challenging and risky, as there is hardly any mouth opening for a mouth guard to be inserted. We devised a new innovative technique with the use of Guedel airway insertion for performing upper GI endoscopy in patients with small mouth opening(trismus) or restricted mouth opening.